EDUCATIONAL MIXED MARKETING STRATEGIES AND SUSTAINABLE COMPETITIVE ADVANTAGES IN MEDIATING THE INFLUENCE OF MARKETING ORIENTATION OVER MARKETING PERFORMANCE - Muhsin, Muhsin; Slamet, Achmad; Wahyudin, Agus (Universitas Negeri Semarang, 2017)
Currently, the Private Universities (PTS) Management faced with the problems of increasing demand from its stakeholders. On the one hand the fulfillment of quality demands and quality graduates is satisfactory, on the other hand, the resources owned by the PTS is limited. In addition, PTS is also faced with the issue of competition ever increasing harsh: low input, limited resources, especially human resource, and funding. Insufficient resources lead to lower service quality. Low service satisfaction and service quality provide a negative impact on the interest to select or enter PTS. Therefore, it demands a highly credible marketing orientation. Research on the influence of marketing orientation over marketing performance turned out to have a contradiction. Therefore, this study is focused on the variable of mediating mixed marketing strategies and sustainable competitive advantage so as to close the research gap in this study that will be analyzed structurally in order to result in further research. This study was divided into two, namely descriptive and inferential path analyses, employing the SPSS 21. The results showed that in fact the level of marketing orientation, the mixed marketing strategies, and the competitive advantage were in the adequate category, while the marketing performance was experiencing decreases. The results of the path analysis are as follows. The marketing orientation variable affects directly or indirectly (through a mixed marketing strategy and a sustainable competitive advantage) over the marketing performance. The suggestion from this study is the marketing orientation needs to be trained so that optimal impact on the quality of the mixed marketing strategy creates sustainable competitive advantage and improves marketing performance.